Optimal trough concentration of teicoplanin for the treatment of methicillin‐resistant Staphylococcus aureus infection: A systematic review and meta‐analysis. - Hanai, Yuki; Takahashi, Yoshiko; Niwa, Takashi; Mayumi, Toshihiko; Hamada, Yukihiro; Kimura, Toshimi; Matsumoto, Kazuaki; Fujii, Satoshi; Takesue, Yoshio (Journal of Clinical Pharmacy & Therapeutics, 2021)
What is known and objective: It has been recommended that the trough concentration (Cmin) of teicoplanin should be maintained at ≥20 μg/ml for difficult‐to‐treat complicated infections caused by methicillin‐resistant Staphylococcus aureus (MRSA). Conversely, Cmin of teicoplanin of at least 10 μg/ml is required for non‐complicated MRSA infections. Considering the low incidence of nephrotoxicity for teicoplanin, Cmin = 15–30 μg/ml has been suggested for most MRSA infections. Thus, we assessed the clinical efficacy and adverse effects of teicoplanin at this target Cmin. Methods: We searched electronic databases (PubMed, Cochrane Central Register of Controlled Trials and Ichushi‐Web) to identify eligible studies. Studies were included if they provided the incidence of treatment success, mortality in patients with MRSA infection, and/or hepatotoxicity and nephrotoxicity according to the Cmin range. Results and discussion: Four trials assessing clinical success (n = 299) and three studies assessing adverse effects (n = 546) were included. Cmin = 15–30 μg/ml significantly increased the probability of treatment success compared with Cmin < 15 μg/ml (odds ratio [OR] = 2.68, 95% confidence interval [CI] = 1.14–6.32, p = 0.02). The all‐cause mortality rate did not differ between the groups (OR = 0.46, 95% CI = 0.13–1.61, p = 0.22). Cmin = 15–30 μg/ml did not increase the risks of nephrotoxicity (OR = 0.91, 95% CI = 0.49–1.69, p = 0.76) or hepatotoxicity (OR = 0.67, 95% CI = 0.18–2.44, p = 0.54). What is new and conclusion: Teicoplanin therapy using a Cmin target of 15–30 μg/ml is likely to be associated with better clinical responses than Cmin < 15 μg/ml without increasing the risk of adverse effects.